Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Prioritas Bank BJB Syariah Cabang Serang - Dede Rahmatu Zahra; Fani Fauziah; Nurkomalasari; Henny Saraswati; Wahyu Hidayat (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
The purpose of this study was to determine the quality of service related to customer satisfaction at the Serang branch of Bank BJB Syariah. This research is a quantitative research that focuses on testing hypotheses for bipolar data. Data collection techniques through questionnaires are used as a sampling method. To measure each test, the results of 55 main customers of the Serang Branch of the BJB Syariah bank were used which consisted of 22 questions. The results of hypothesis testing show that the quality of service perceived by priority customers of Bank BJB Syariah Serang Branch is very good, influencing customer satisfaction by 87%.